Outcome of children and adolescents with lymphoblastic lymphoma - Oliveira,Maria Christina Lopes Araújo (2015)
Summary Introduction: lymphoblastic lymphoma (LBL) is the second most common subtype of non-Hodgkin lymphoma in children. The aim of this study was to characterize the clinical course of children and adolescents with LBL treated at a tertiary center. Methods: this is a retrospective cohort study of 27 patients aged 16 years or younger with LBL admitted between January 1981 and December 2013. Patients were treated according to the therapy protocol used for acute lymphoblastic leucemia. Diagnosis was based on biopsy of tumor and/or cytological examination of pleural effusions. The overall survival was analyzed using the Kaplan-Meier method. Results: the median age at diagnosis was 11.6 years (interquartile range, 4.6- 13.8). LBL had T-cell origin in 16 patients (59%). The most common primary manifestation in T-cell LBL was mediastinal involvement, in 9 patients (56%). Intra-abdominal tumor was the major site of involvement in patients with precursor B-LBL. Most patients had advanced disease (18 patients – 67%) at diagnosis. Twenty-four patients (89%) achieved complete clinical remission. After a median follow-up of 43 months (interquartile range, 6.4-95), 22 patients (81%) were alive in first complete remission. Five children (18.5%) died, three of them soon after admission and two after relapsing. The probability of survival at five years for 20 patients with de novo LBL was 78% (SD 9.4). Conclusion: our findings confirm the favorable prognosis of children with LBL with an intensive chemotherapy regimen derived from ALL therapy.